1999
DOI: 10.1007/s003830050541
|View full text |Cite
|
Sign up to set email alerts
|

Lipoma of the preputium clitoridis in neonate: an exceptional abnormality different from ambiguous genitalia

Abstract: A lipoma of the preputium clitoridis was found in a newborn girl. Ambiguous genitalia was first suspected. Surgery was successfully performed at 5 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
7
0
3
Order By: Relevance
“…In 1982, Fukamizu et al (3) reported a case of a large pedunculated vulvar lipoma in an infant, which had been present since birth. In 1999, Van Glabeke et al (4) reported a case of a neonate with a vulvar lipoma observed in the preputium clitoridis. Kehagias et al (5) described CT findings for a large pedunculated vulvar lipoma measuring 17 × 13 × 7 cm in a 35-yr-old woman and concluded that ultrasound, CT and magnetic resonance imaging (MRI) were useful tools to reveal the lipomatous consistency of these tumors and to differentiate them from vulvar cysts.…”
Section: Discussionmentioning
confidence: 99%
“…In 1982, Fukamizu et al (3) reported a case of a large pedunculated vulvar lipoma in an infant, which had been present since birth. In 1999, Van Glabeke et al (4) reported a case of a neonate with a vulvar lipoma observed in the preputium clitoridis. Kehagias et al (5) described CT findings for a large pedunculated vulvar lipoma measuring 17 × 13 × 7 cm in a 35-yr-old woman and concluded that ultrasound, CT and magnetic resonance imaging (MRI) were useful tools to reveal the lipomatous consistency of these tumors and to differentiate them from vulvar cysts.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, a well-demarcated pedunculated mass was a common finding [4,5,8,9], and presentation as ambiguous genitalia were found [3,6]. However, nonpedunculated vulvar swelling because of subcutaneous fat deposition has also been reported [10,11].…”
Section: Discussionmentioning
confidence: 89%
“…In a review of the relevant literature, approximately 70 cases of vulvar lipomas have been reported, and all of the reported literature was limited to case reports [2][3][4][5][6][7][8][9][10][11]. The incidence of vulvar lipomas in children is so low that fewer than 10 cases have been reported [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rare clitoral neoplasms have been confused with ambiguous genitalia. 8,9 Whether or not to surgically correct the genitalia of individuals with intersex conditions is a matter of great debate, with advocates on both sides, and is beyond the scope of this discussion. There are several reviews on the evaluation and management of these patients.…”
Section: Congenital Anomalies and Intersex Conditionsmentioning
confidence: 99%